Complement System as a Target for Therapies to Control Liver Regeneration/Damage in Acute Liver Failure Induced by Viral Hepatitis. (8th October 2018) - Melgaço, Juliana Gil; Veloso, Carlos Eduardo; Pacheco-Moreira, Lúcio Filgueiras; Vitral, Claudia Lamarca; Pinto, Marcelo Alves
Abstract : The complement system plays an important role in innate immunity inducing liver diseases as well as signaling immune cell activation in local inflammation regulating immunomodulatory effects such as liver damage and/or liver regeneration. Our aim is to evaluate the role of complement components in acute liver failure (ALF) caused by viral hepatitis, involving virus-induced ALF in human subjects using peripheral blood, samples of liver tissues, and ex vivo assays. Our findings displayed low levels of C3a in plasma samples with high frequency of C3a, C5a, and C5b/9 deposition in liver parenchyma. Meanwhile, laboratory assays using HepG2 (hepatocyte cell line) showed susceptibility to plasma samples from ALF patients impairing in vitro cell proliferation and an increase in apoptotic events submitting plasma samples to heat inactivation. In summary, our data suggest that the complement system may be involved in liver dysfunction in viral-induced acute liver failure cases using ex vivo assays. In extension to our findings, we provide insights into future studies using animal models for viral-induced ALF, as well as other associated soluble components, which need further investigation.